Formulas of Acoustics - Mechel, Fridolin P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This collection of formulas has been written by applied scientists and industrial engineers for design professionals and students who work in engineering acoustics. It is subdivided into the most important fields of applied acoustics, each dealing with a well-defined type of problem. It provides easy and rapid access to profound and comprehensive information. In order to keep the text as concise as possible, the derivation of a formula is described only as far as necessary for its understanding. The interested reader can refer to the original source of the result. In addition to formulas, useful principles and computational procedures are given.
Editorials -- General Linear Fluid Acoustics -- Equivalent Networks -- Reflection of Sound -- Scattering of Sound -- Radiation of Sound -- Porous Absorbers -- Compound Absorbers -- Sound Transmission -- Duct Acoustics -- Muffler Acoustics -- Capsules and Cabins -- Room Acoustics -- Flow Acoustics -- Analytical and Numerical Methods in Acoustics -- Variational Principles in Acoustics -- Elasto-Acoustics -- Ultrasound Absorption in Solids -- Index.
Keywords: Engineering; Acoustics; Vibration; Dynamical systems; Dynamics; Mechanical engineering; Civil engineering; Engineering; Vibration, Dynamical Systems, Control; Acoustics; Mechanical Engineering; Civil Engineering; Electronic books